From Policy to Practice: Gender Sensitivity and Persistent Biases in Tubod, Lanao del Norte, Philippines - Khalid Datu Daud; Jamaliah Aimo Hadali (Az-Zahra: Journal of Gender and Family Studies, 2026)
This study examines gender sensitivity in Tubod, Lanao del Norte, Philippines, with an emphasis on political competition, career promotion, education, and family roles. Although national-level research shows gender inequities in the Philippines, there is little empirical information on how gender-sensitive strategies work across several areas. Following a gender-mainstreaming approach, we conducted a descriptive survey with a structured questionnaire to assess respondents' awareness of gender issues and perceived fairness in the four areas. The analysis included descriptive statistics and group comparisons based on gender, age, and education. Results show higher perceived gender parity in political competition and job promotion, but education and family roles reveal persistent gendered expectations: most respondents said girls/women face educational barriers, and several others supported traditional family-role norms that limit women's career mobility. These domain-specific patterns indicate that while local governments and workplaces in Tubod have begun to implement gender-sensitive initiatives, deeply rooted cultural norms continue to perpetuate inequality in schooling and the family. The study provides the first community-level baseline for Tubod, highlighting where interventions should be focused — school-based gender-awareness programs and family-targeted community campaigns — and making locally tailored suggestions to legislators and educators. Convenience sampling and cross-sectional design are limitations; longitudinal and probability-sample studies should be used to examine the causal effects of gender-sensitive policy